A group of youth organizations - overview of the political participation of youth - Garcés Montoya, Ángela (Última Década, 2020)
As part of the investigation «juvenile political participation practices from which youth build citizenship in the city of Medellín», This article suggests ways to recognize the youth group that travel between organizations and youth groups identified as two divergent forms of political participation of youth. In principle it is possible to name the youth organization as «officially» social participation, community, political and civic youth, they are based on the recognition and acceptance of structures, objectives and collective interests are based on formal institutions own the world adult, such as youth ministry, scout groups, political parties, rural groups. Other forms of youth participation, youth are based on actual interest, this highlights the cultural groups, musical, aesthetic and resistance. Between them we’ll see how youth group forms vary between organizations and youth groups.